2013
DOI: 10.3390/rs5020810
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Variability of AVHRR-Derived NPP in India

Abstract: Abstract:In this paper, we estimate the trends and variability in Advanced Very High Resolution Radiometer (AVHRR)-derived terrestrial net primary productivity (NPP) over India for the period 1982-2006. We find an increasing trend of 3.9% per decade (r = 0.78, R 2 = 0.61) during the analysis period. A multivariate linear regression of NPP with temperature, precipitation, atmospheric CO 2 concentration, soil water and surface solar radiation (r = 0.80, R 2 = 0.65) indicates that the increasing trend is partly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 37 publications
(66 reference statements)
6
44
1
1
Order By: Relevance
“…Empirically upscaled estimates of GPP in East Asia revealed a significant reduction in the summer of 2003 in response to meteorological anomalies [30]. Increased GPP has also been identified using diagnostic terrestrial biosphere models in China [31] and India [28].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Empirically upscaled estimates of GPP in East Asia revealed a significant reduction in the summer of 2003 in response to meteorological anomalies [30]. Increased GPP has also been identified using diagnostic terrestrial biosphere models in China [31] and India [28].…”
Section: Introductionmentioning
confidence: 90%
“…In Southeast Asia, interannual variations in vegetation indices were found to be largely determined by the El Niño Southern Oscillation [27]. Furthermore, vegetation greenness was found to have increased in India because irrigated areas and fertilization use increased [28]. However, this increase in vegetation greenness has stagnated in recent years [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is significant variability among these models' results due to differences in formulation of ecosystem processes, underlying assumptions for their formulation in these models, and the uncertainties associated with observations used in understanding these processes [14,15]. For assessing NPP and its spatial and temporal trends, quite often a combination of models and observational proxies (e.g., NDVI) are used [16,17] to ensure the reliability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, de Jong et al (2011) found that many forested biomes experienced a decline in vegetation greenness. There is still no consistent result on trends of global vegetation activity (Bala et al, 2013).…”
Section: Introductionmentioning
confidence: 91%